Potential Chemopreventive Effects of Dietary Combination of Phytochemicals against Cancer Development - Takuji Tanaka; Ryogo Aoki; Masaru Terasaki (MDPI AG, 2023)
Cancer remains a major cause of cancer-related death worldwide. Over 70% of epithelial malignancies are sporadic and are related to lifestyle. Epidemiological studies suggest an inverse correlation between cancer incidence and fruit and vegetable intake. Numerous preclinical studies using in vitro (cell lines) and in vivo animal models of oncogenesis have reported the chemopreventive effects of dietary phytochemical agents through alterations in different biomarkers and signaling pathways. However, there is contrasting evidence from preclinical studies and clinical trials. To date, the most studied compounds include curcumin, resveratrol, isoflavones, green tea extract (epigallocatechin gallate), black raspberry powder (anthocyanins and ellagitannins), bilberry extract (anthocyanins), ginger extract (gingerol derivatives), and pomegranate extract (ellagitannins and ellagic acid). Overall, the clinical evidence of the preventive effects of dietary phytochemicals against cancer development is still weak, and the amount of these phytochemicals needed to exert chemopreventive effects largely exceeds the common dietary doses. Therefore, we propose a combination treatment of natural compounds that are used clinically for another purpose in order to obtain excess inhibitory efficacy via low-dose administration and discuss the possible reasons behind the gap between preclinical research and clinical trials.